Intimate partner violence, suicidality, and self-harm: a probability sample survey of the general population in England. (July 2022) - McManus, Sally; Walby, Sylvia; Barbosa, Estela Capelas; Appleby, Louis; Brugha, Traolach; Bebbington, Paul E; Cook, Elizabeth A; Knipe, Duleeka
Summary: Background: Intimate partner violence (IPV) is a recognised risk factor for psychiatric disorders. There is little current evidence on IPV and self-harm and suicidality, and we therefore aimed to investigate the associations between experience of lifetime and past-year IPV with suicidal thoughts, suicide attempt, and self-harm in the past year. Methods: We analysed the 2014 Adult Psychiatric Morbidity Survey, a cross-sectional survey of 7058 adults (aged ≥16 years) in England, which used a multistage random probability sampling design and involved face-to-face interviews. Participants were asked about experience of physical violence and sexual, economic, and emotional abuse from a current or former partner, and about suicidal thoughts, suicide attempts, and self-harm. Other adversities were recorded through an adapted version of the List of Threatening Experiences. Multivariable logistic regression models quantified associations between different indicators of lifetime and past-year IPV, with past-year non-suicidal self-harm, suicidal thoughts, and suicide attempts. All analyses were weighted. Findings: Using weighted percentages, we found that a fifth (21·4%) of 7058 adults reported lifetime experience of IPV, and that 27·2% of women and 15·3% of men had experienced IPV. Among women, 19·6% had ever experienced emotional IPV, 18·7% physical IPV, 8·5% economic IPV, and 3·7% sexual IPV, which was higher than in men (8·6%, 9·3%, 3·6%, and 0·3%, respectively). Findings for ethnicity were unclear. Lifetime prevalence of IPV was higher in those living in rented accommodation or deprived neighbourhoods. Among people who had attempted suicide in the past year, 49·7% had ever experienced IPV and 23·1% had experienced IPV in the past year (including 34·8% of women and 9·4% of men). After adjusting for demographics, socioeconomics, and lifetime experience of adversities, the odds ratio of a past-year suicide attempt were 2·82 (95% CI 1·54–5·17) times higher in those who have ever experienced IPV, compared with those who had not. Fully adjusted odds ratios for past-year self-harm (2·20, 95% CI 1·37–3·53) and suicidal thoughts (1·85, 1·39–2·46) were also raised in those who had ever experienced IPV. Interpretation: IPV is common in England, especially among women, and is strongly associated with self-harm and suicidality. People presenting to services in suicidal distress or after self-harm should be asked about IPV. Interventions designed to reduce the prevalence and duration of IPV might protect and improve the lives of people at risk of self-harm and suicide. Funding: UK Prevention Research Partnership.